Development of A Wide Axial Ratio Bandwidth Circularly Polarized Antenna for Spectrum Occupancy Measurement Campaign - Shirgan, Siddharudha Shivputra; Bombale, Uttam Laxman (Recent Advances in Mathematical Research and Computer Science Vol. 3, 2021)
Spectrum measurement campaigns around the world have confirmed that a significant amount of radio spectrum is underutilised. According to the literature, the majority of spectrum measurement campaigns use commercially available antennas. A novel circularly polarised wide axial ratio bandwidth circularly polarised microstrip antenna is designed for Spectrum Occupancy Measurement in this communication. The antenna has a broad -10 dB impedance bandwidth from 700 MHz to 2.9 GHz, as well as a broad -3dB axial ratio bandwidth from 1.5 GHz to 2.7 GHz. The antenna prototype has been built, and the simulated results agree very well with the measured results. Following that, the antenna's spectrum sensing ability is validated using a spectrum sensing measurement setup, which shows excellent spectrum sensing ability, -24 to -31.5 dBm in GSM 900 MHz, LTE 2.1 GHz, and ISM 2.4 GHz bands in an outdoor environment. The proposed antenna is compact , portable, and simple to integrate into the spectrum sensing measurement setup.The spectrum sensing ability of the proposed antenna is verified through the spectrum occupancy measurement setup, and results are found better than the antenna used in literature.